2018
DOI: 10.1097/lbr.0000000000000506
|View full text |Cite
|
Sign up to set email alerts
|

Chylothorax From Gorham-Stout Disease

Abstract: Chylothorax is one of the presenting features in many disorders including malignancy. Thorough investigation is often required for establishing the etiology of chylothorax. Unfortunately, despite appropriate work-up etiology of pleural effusion cannot be established. We report a case of chylothorax associated with multiple lytic bony lesions, finally diagnosed as a case of Gorham-Stout disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The most common traumatic causes of chylothorax are cardiothoracic surgical procedures. Non-traumatic causes include malignancy, tuberculosis, liver cirrhosis, and malformations[ 3 , 11 , 12 ]. Romero et al [ 13 ] reported that chylous ascites could present as chylothorax in patients with liver cirrhosis, due to communications between the thoracic and peritoneal cavity and lower pressure in the pleural cavity.…”
Section: Discussionmentioning
confidence: 99%
“…The most common traumatic causes of chylothorax are cardiothoracic surgical procedures. Non-traumatic causes include malignancy, tuberculosis, liver cirrhosis, and malformations[ 3 , 11 , 12 ]. Romero et al [ 13 ] reported that chylous ascites could present as chylothorax in patients with liver cirrhosis, due to communications between the thoracic and peritoneal cavity and lower pressure in the pleural cavity.…”
Section: Discussionmentioning
confidence: 99%
“…[24] The mortality rate of GSD is high and the prognosis is poor in patients complicated with chylothorax. [12] The appearance of chylothorax was always fatal with death resulting from respiratory insufficiency, malnutrition, lymphopenia, and superimposed infection. [25]…”
Section: Discussionmentioning
confidence: 99%
“…[8,9] The chylous pericardial and pleural effusions can complicate the disease and lead to death in severe cases. [1012] The medical treatment for GSD includes anti-osteoclastic medications (bisphosphonates), radiotherapy, thoracic duct ligation, interferon, and cement augmentation. [13] In this report, we show a case of Gorham disease involving thoracic spine with chylous pericardial and pleural effusions detected by 99m Tc-sulfur colloid (SC) single photon emission computed tomography/computed tomography (SPECT/CT).…”
Section: Introductionmentioning
confidence: 99%
“…Surgery also plays a key role in thoracic complications, such as chylothorax or even minor pleural fluid leakage, which have been treated with pleural drainage (119,149,151,152), pleurectomy, pleurodesis (64,153,154) and/ or thoracic duct ligation or embolization (14,27,65,155). In most of the cases, the best outcome has been obtained by combining these surgical techniques rather than using them in isolation (154,156).…”
Section: Surgical Treatmentmentioning
confidence: 99%